State-of-the-Art Review on Botanical Hybrid Preparations in Phytomedicine and Phytotherapy Research: Background and Perspectives - Alexander Panossian; Terry Lemerond; Thomas Efferth (MDPI AG, 2024)
Background: Despite some evidence supporting the synergy concept, the commonly known assumption that combinations of several herbs in one formulation can have better efficacy due to additive or synergistic effects has yet to be unambiguously and explicitly studied. Study aim: The study aimed to reveal the molecular interactions in situ of host cells in response to botanical hybrid preparations (BHP) intervention and justify the benefits of implementing BHP in clinical practice. Results: This prospective literature review provides the results of recent clinical and network pharmacology studies of BHP of Rhodiola rosea L. (Arctic root) with other plants, including Withania somnifera (L.) Dunal (ashwagandha), (Camellia sinensis (L.) Kuntze (green tea), Eleutherococcus senticosus (Rupr. and Maxim.) Maxim. (eleuthero), Schisandra chinensis (Turcz.) Baill. (schisandra), Leuzea carthamoides (Willd.) DC., caffeine, Cordyceps militaris L., Ginkgo biloba L.(ginkgo), Actaea racemosa L. (black cohosh), Crocus sativus L. (saffron), and L-carnosine. Conclusions: The most important finding from network pharmacology studies of BHP was the evidence supporting the synergistic interaction of BHP ingredients, revealing unexpected new pharmacological activities unique and specific to the new BHP. Some studies show the superior efficacy of BHP compared to mono-drugs. At the same time, some a priori-designed combinations can fail, presumably due to antagonistic interactions and crosstalk between molecular targets within the molecular networks involved in the cellular and overall response of organisms to the intervention. Network pharmacology studies help predict the results of studies aimed at discovering new indications and unpredicted adverse events.